VIS-NIR portable espectrometer for nondestructive assessment of maturity and quality of ‘Gala’ apples Espectrômetro VIS-NIR portátil para análise não destrutiva da maturação e qualidade de maçãs ‘Gala’ - Moraes J.C.V.* (2023)
© 2023, Sociedade Brasileira de Fruticultura. All rights reserved.Visible and near infrared (VIS-NIR) spectroscopy is a non-destructive, fast, practical and reliable technique to determine maturity and quality attributes in apple fruit. However, the effects of cultivar and growing conditions on the predictive performance of the equipment must be determined before its commercial application in the apple industry. This study was carried out to evaluate the efficiency of a VIS-NIR portable spectrometer for fast and non-destructive determination of quality attributes in apples of the ‘Gala’ group (‘Maxi Gala’, ‘Royal Gala’, ‘Imperial Gala’ and ‘Galaxy’) harvested in three commercial orchards (corresponding to the production sites: Vacaria, Fraiburgo and São Joaquim) in Southern Brazil. At the commercial harvest and after three months of cold storage (1.5 ± 0.3 ºC and relative humidity of 92 ± 2%), fruit were assessed in terms of spectral data in the wavelength range between 310 and 1100 nm with a VIS-NIR portable spectrometer. After collecting the spectral data, fruit were submitted to physicochemical analysis of dry matter (DM), soluble solids content (SSC), flesh firmness and texture. The calibration models were developed using three sets of spectral and physicochemical data: (1) without separating by cultivar and orchard; (2): separating by cultivar, regardless of orchard; (3): separating by cultivar and by orchard. The calibration models were obtained by the partial least squares (PLS) regression technique. The accuracy of the calibration models for each dataset was evaluated in the validation step considering the values of the relative root mean square error of cross-validation (RMSECVr ≤ 10%). Models developed for each cultivar in each orchard (location) were more accurate and efficient to assess DM, SSC and flesh firmness, compared to the models developed for each cultivar, regardless of orchard, or without separating by cultivar and by orchard. Therefore, VIS-NIR spectrometer is a promising tool for the rapid and non-destructive analysis of quality attributes in ‘Gala’ apples. However, the equipment must be calibrated for each cultivar (‘Maxi Gala’, ‘Royal Gala’, ‘Imperial Gala’ and ‘Galaxy’) and growing condition (orchard) in order to obtain more precise analyses of DM, SSC and flesh firmness in the fruit.